Morphological Features of Liver Reactivity After Intranatal Dexamethazone Influence - Hryhorieva, O. A.; Bohdanov, P. V.; Guminskiy, Y. Y.; Pivtorak, V. I.; Kovalchuk, O. I.; Matvieishyna, T. M.; Chugin, S. V.; Tavrog, M. L.; Vovchenko, M. B.; Grynivetska, N. V.; Григор'єва, Олена Анатоліївна; Богданов, Павло Валерійович; et al. (My University, 2022)
The study included the livers of 144 white laboratory rats from 1 to 90 days of life. All animals were conditionally divided into 3 groups: Group I - intact animals, which were born from healthy rats without any dexamethazone administration during pregnancy; group II - control animals, which were exposed to antenatal intrafetal administration of 0.05 ml saline solution on the 18th day of prenatal development; group III - experimental animals, which were exposed to antenatal dexamethazone administration at 18th day of prenatal development. The absolute and relative mass of the liver was calculated. For light microscopy, sections were stained with hematoxylin and eosin. Detection of β-D-galactose carbohydrate residues was performed using a Lectin from Ricinus communis Agglutinin (RCA) by standard methods, using standard set of reagents "LectinTest" (Lviv). Quantitative and qualitative morphological characteristics of the liver were studied. Analysis of the obtained results was conducted by means of statistical methods with the use of computer license program «Statistica for Windows 13» (StatSoft Inc., № JPZ804I382130ARCN10-J). It was found that in rats after intrauterine administration of dexamethasone morphological changes in the liver are determined within three months after birth, which are manifested by changes in absolute and relative liver mass, as well as the rate of increase in absolute organ mass. The relations between hepatic membranes, vessels, connective tissue, cells of hematopoietic centers change. Changes in the cellular composition of the liver lobes are detected. The introduction of dexamethasone leads to changes in the formation of connective tissue in the liver, namely an increase in the amount of connective tissue in the long-term follow-up. In rats after intrauterine administration of dexamethasone from the 14th to the 90th day there is an increase in the relative area occupied by connective tissue in the liver, reaching statistical significance on the 30th day. In animals after intrauterine administration of dexamethasone on the 1st day of life increases the absolute number of mononuclear hepatocytes in the central, and in the peripheral zone is detected. In the group of experimental animals, after intrauterine administration of dexamethasone there is a decrease in the relative area occupied by PAS-positive structures in the central zone from the 7th to the 21st day. In the peripheral zone, the decrease is more pronounced and is observed during the first three weeks after birth.
Keywords: liver; intranatal dexamethazone influence; lymphocytes; PAS-reaction